Epitaxial growth of transition metal nitrides by reactive sputtering - Hörich, Florian; Lüttich, Christopher; Grümbel, Jona; Bläsing, Jürgen; Feneberg, Martin; Dadgar, Armin; Goldhahn, Rüdiger; Strittmatter, André (Frontiers in Materials, 2025)
Implementing transition metal nitride (TM-nitride) layers by epitaxy into group-III nitride semiconductor layer structures may solve substantial persisting problems for electronic and optoelectronic device configurations and subsequently enable new device classes in the favorable nitride semiconductor family. As a prominent example, the integration of the group-III-transition metal nitride AlScN enabled an improved performance of GaN based transistor structures due to stronger polarization fields as has been recently demonstrated. For other transition metal nitrides (TMNs) and their alloys with group-III nitrides a range of other interesting properties is expected to enable novel devices and applications. We investigated the compatibility of TM-nitride layers with the growth of GaN-based structures on silicon substrates. As we show TiN layers are compatible and particularly suited as highly conducting, metallic-like buffer layer enabling true vertical conduction without elaborate backside processing. Also, we demonstrate epitaxial growth of alloys based on ScN and AlN as well as of HfN layers on Si(111) substrates by reactive sputtering using high purity gases and targets. Particularly, we analyzed the crystal structure and the quality of Sc-rich AlxSc1-xN. For HfN layers, we find a unique impact on the growth polarity of MOVPE-grown GaN layers on Si(111) which changes to N-polar growth. This represents a simple and technologically scalable approach for N-polar GaN-based layers on Si substrates.